Pengembangan Lembar Kerja Peserta Didik (LKPD) Berorientasi Higher Order Thinking Skill (HOTS) Pada Materi Mengkreasikan Puisi Rakyat Kelas VII SMP Negeri 06 Jeneponto - Meri Hariratul Jannah; A. Fitriani Suryadi; Besse Nurul Hikmah (Lembaga Penelitian Mahasiswa Penalaran UNM, 2022)
This study aims to train students in critical, reflective, metacognitive, and creative thinking through the development of student worksheets (LKPD) on the learning process and the quality of learning outcomes. The type of research used is research and development (R&D) which is valid and practical. The research and development stage refers to the 4-D model (Define, Design, Development, Disseminate). The data instrument in this study was a student response questionnaire. The questionnaire was developed with 4 assessment categories, namely strongly agree (score 4), agree (score 3), disagree (score 2), strongly disagree (score 1). Data analysis techniques. This development research used quantitative descriptive analysis through assessment sheets, observation sheets and response questionnaires and student learning outcomes. Data analysis techniques start from data validation results of student worksheets (LKPD) and data on practical results of LKPD. The results of the study consisted of two, namely (1) the validity of the LKPD validity assessment instrument and the questionnaire validity assessment instrument, (2) practicality in the form of a questionnaire of educator responses and students' responses to LKPD. The results of the research from the two aspects carried out include aspects of validity and practicality that meet the criteria and are suitable for use.